Evaluasi Program Bimbingan dan Konseling - Arsini, Yeni; Lubis, Siti Rahayu; Lubis, Swaibah Aslamiah; Azzahra, Nadya (Lembaga Yasin AlSys, 2024)
This journal examines the evaluation of guidance and counseling (BK) programs in the Indonesian education context using library research methods. This assessment is important to ensure the effectiveness of school counseling services. Evaluation includes the definition of the BK program, program mission, evaluation objectives, types of evaluation, stages of evaluation and the importance of the evaluation. Evaluation of the BK program helps supervising teachers monitor the effectiveness and efficiency of services, evaluate program processes and results, and improve and develop programs to improve the quality of services provided to students. Evaluation also helps plan program improvements and understand the factors that influence its implementation. In short, it can be said that evaluation of the BK program is very important to improve the quality of education and development of students.